Implementation of Superior Branding and Governance Strategies in Improving The Existence of Early Childhood Institutions (Study on Kb/Tk Ummahat Aisyiyah Cemani, Sukoharjo) - Suranto; Sabar Narimo; Moc. Chairil Asmawan; Azarin Carissa Putri Laksmi; Adelia Dinda Maharani; Andriyani Puji Lestari (Abdi Psikonomi, 2026)
This community service activity aims to increase the existence of KB/TK Ummahat Aisyiyah Cemani through the implementation of an integrated branding and superior governance strategy. The main problems of partners include weak school branding, limited promotion, conventional governance, and suboptimal community involvement and partnerships. The methods used are participatory, educational, and applicative approaches through the stages of socialization, training and workshops, mentoring, partnership collaboration, and monitoring and evaluation. The programs carried out include parenting activities, coloring competitions and trial classes, grand recitations and social activities, social media development, school governance assistance, and procurement of promotional media. The results of the activity showed an increase in school visibility, parental and community involvement, as well as improvements in a more professional and systematic governance system. The use of social media has also proven effective in expanding the reach of promotion and building a positive image of the institution. In addition, collaboration with various stakeholders strengthens the network's network and the sustainability of the program. Thus, the superior branding and governance strategies implemented are able to increase the existence and competitiveness of KB/TK Ummahat Aisyiyah Cemani. This service model can be a reference for other Early Childhood Education institutions in facing competitive challenges in the digital era.